No transfer of the non-regulated mycotoxins, beauvericin and enniatins, from feeds to farmed fish reared on plant-based diets - Nácher-Mestre, Jaime; Beltrán, Eduardo; Strachan, Fiona; Dick, James R; Pérez-Sánchez, Jaume; Berntssen, Marc H G; Tocher, Douglas R (Food Chemistry, 2020)
Concern about the risk of exposure to emerging plant-derived mycotoxins such as beauvericin and enniatins has been addressed by the European Commission who requested the European Food Safety Authority for a scientific opinion on their risk to human and animal health. The studied mycotoxins were found in feeds with enniatin B and beauvericin at average concentrations of 19.9 μg/kg and 30 μg/kg, respectively. In all cases, concentrations of all the mycotoxins analyzed were below quantification limits (< 0.1 μg/kg) in fish samples (n = 82). The present work provides comprehensive and traceable data of emerging mycotoxins in plant-based aquafeeds and fish reared on the feeds, responding to increasing concerns about safety of farmed fish fed on sustainable feeds. On the basis of data reported, there was no transfer of the emerging mycotoxins, beauvericin and enniatins, from feeds to fish and so, no risk for human consumption.